2021
DOI: 10.1002/nur.22195
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a nurse‐led mindfulness stress‐reduction intervention on diabetes distress, diabetes self‐management, and HbA1c levels among people with type 2 diabetes: A pilot randomized controlled trial

Abstract: People with diabetes frequently have elevated diabetes distress. Although mindfulness‐based stress reduction (MBSR) therapy has been shown effective in reducing diabetes distress, it has only been delivered by psychologists or a multidisciplinary team with an attrition rate of up to 39%, which limits its dissemination to a broader audience. This study was aimed to pilot evaluate the feasibility of a nurse‐led MBSR therapy and explore its potential efficacy amongst people with type 2 diabetes mellitus. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Figure 2 presents the risk of bias in the studies included. Overall, 4 of 9 studies showed low bias, 26,42,44,45 whereas 5 studies showed some concerns. [27][28][29]43,46,47 In the domain of Randomization Process, 5 studies showed low risk of bias, 26,42,[44][45][46] whereas 4 studies showed some concerns, mainly related to lack of clear information about concealment of allocation sequence.…”
Section: Risk Of Biasmentioning
confidence: 98%
See 4 more Smart Citations
“…Figure 2 presents the risk of bias in the studies included. Overall, 4 of 9 studies showed low bias, 26,42,44,45 whereas 5 studies showed some concerns. [27][28][29]43,46,47 In the domain of Randomization Process, 5 studies showed low risk of bias, 26,42,[44][45][46] whereas 4 studies showed some concerns, mainly related to lack of clear information about concealment of allocation sequence.…”
Section: Risk Of Biasmentioning
confidence: 98%
“…28,29 Thus, 9 studies were used in this review. Eight of the studies were 2-arm RCTs, [26][27][28][29]42,43,[45][46][47] and 1 study was a 3-arm RCT. 44 As addressed previously, in the meta-analysis, 2 of the 3 arms (the intervention group and usual care group) were used.…”
Section: Characteristics Of Articles and Interventions Includedmentioning
confidence: 99%
See 3 more Smart Citations